Deconstruction of Malaysian agro-wastes with inexpensive and bifunctional triethylammonium hydrogen sulfate ionic liquid - Shikh Mohd Shahrul Nizan Shikh Zahari; Amin A.T.M.; Halim N.M.; Rosli F.A.; Halim W.I.T.A.; Samsukamal N.A.; Sasithran B.; Ariffin N.Z.; Azman H.H.; Hassan N.H.; Othman Z.S. (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus